PENERAPAN METODE DISKUSI SYNDICATE GROUP UNTUK MENINGKATKANPEMAHAMAN MAHASISWAPADA KONSEP DASAR PENGANTAR ILMU EKONOMI - Wahyono, - (Dinamika Pendidikan, 2009)
The objectives of this study are to improve the learning quality Introduction to Economics, to improve studentsÃ¢â¬â¢ spirit in learning, to improve lecturersÃ¢â¬â¢ skill in developing learning model and media and ÃÂ also to improve studentsÃ¢â¬â¢ achievement in learning. This study was class action research consists of three cycles. Result of study showed studentsÃ¢â¬â¢ achievement was improving on each cycle. StudentsÃ¢â¬â¢ learning completeness before applying syndicate group discussion method was 0%, after applying syndicate group discussion group; studentsÃ¢â¬â¢ achievement after final test was 94%. StudentsÃ¢â¬â¢ interest, activeness and relationship in learning process with range 1-4, the result was good (3.2). Result of observation related to lecturersÃ¢â¬â¢ skill in managing the learning process which used map concept method with range1-4 showed a good result with average of cycle 1, cycle 2 and cycle 3 was 3.2. That score was the average of all aspects investigated on three cycles. Based on result of study, it was suggested that for lecturers of Introduction of Economics subject to apply syndicate group discussion method in teaching-learning process. This methodwas approved to improve studentsÃ¢â¬â¢ ability to analyze the case and understand the concepts of Introductions to Economics. This was because students are given opportunity to do research in the field related to the topic and then find the problems that will be discussed in the class. Thus, students are usual to think critically and analytically to face a case. And finally, students can find the topics concepts. Moreover, result of study can be applied for other subjects because this study gives the positive impact. Key words: Syndicate Group Discussion Method, Basic Concepts of Introduction to Economics.